EDITORIAL (American Journal of Islam and Society, 1993)
The news of Professor Mahmoud Abu Saud’s death has saddened usall. For several decades, he has been a prominent figure in the seminarsand conferences of the Association of Muslim Social Scientists (AMSS),the International Institute of Islamic Thought (IIIT), the Islamic Societyof North America (ISNA), the American Muslim Council (AMC), andother Islamic and interfaith organizations. His passionate commitment tothe reconstruction of Islamic thought, as well as his tireless involvementin writing, lecturing, and touring from country to country and from cityto city, were a great inspiration to our young scholars. As a learnedscholar, Social scientist, and, in particular, an economist, friend, and mentor,he will be missed in many forums. He served as a referee for theAmerican Journal of Islamic Social Sciences (AJISS), and his commentswere always objective and straightforward. His ideas, ideals, and intellectualand moral heritage will continue to inspire his friends andstudents. We pray that Almighty Allah will cover him with His mercyand also grant us patience and help us to emulate some of his extra-The growth and development of MISS was one of the aspitations ofthe late Mahmoud Abu Saud. Our constant struggle to enhance the intellectualcontent of the journal will be a source of reward to the departedsoul of that great mujdhid. For verily “we belong to Allah and to Him wereturn.“This issue begins with Mahmoud Dhaouadi’s paper on Islamicknowledge and the rise of the new science. In the last few decades,Mahmoud Dhaouadi argues, western science has begun to shift from whatis called classical science to new science. This vision of the emergingnew science promises to heal the division between matter and spirit andto do away with the mechanical dimension of the world. However, theprocess of reconciliation between religion and science in modem westernculture still faces a great many hurdles. Islam, on the other hand, looksat knowledge and science as a continuum whereby divine and humanknowledge and science both cooperate with and complement each other.He gives examples from the practices of classical Muslim scholars, suchas Ibn Khaldin, who based their research on this approach. Knowledge ...